Sejarah Sosial Ekonomi Masyarakat Home Industri Pendaur Ulang Desa Kupang Jabon Sidoarjo 2011 - 2016 - Muhammad Bahrul Alamsyah (P-SEMART JOURNAL, 2021)
This thesis is entitled History of Social Economic Community Home Industry Recycler in Kupang, Jabon Sidoarjo Village, 2011-2016. This type of research is a qualitative research with the research approach used is phenomenology and sociology. The data sources of this research are primary data and secondary data. Furthermore, the data collection methods used in this study were observation, interviews, and documentation. The results of this study indicate that the social background of the scavengers at the Jabon Final Disposal Site are people who work as community scavengers whose economic conditions are weak so that they become scavengers. The economic situation of the Jabon people is fairly low, so most people choose to work as scavengers. It is hoped that the government will pay more attention to the social conditions of the scavenger communities, especially their economic conditions, and also for the children of scavengers to receive a better education so that their future can be better.